The impact of migrants' knowledge about their social rights on their subjective wellbeing - Seibel, Verena (Frontiers in Political Science, 2023)
In this contribution I examine the role of migrants’ knowledge about their social rights (system knowledge) for their subjective well-being. I expect system knowledge to be positively associated with migrants’ well-being. Migrants who are well informed about their social rights have better access to resources that are crucial for their well-being such as healthcare or financial security. Moreover, I expect that knowledge in certain domains, such as healthcare, matter more than knowledge in other domains. I make use of the Migrants’ Welfare State Attitudes (MIFARE) data which includes the perspective of migrants from nine different origin countries across three receiving countries: Denmark, the Netherlands, and Germany. Results indicate that migrants differ extensively in their social rights knowledge. Moreover, migrants’ knowledge about their social rights is indeed positively associated with subjective well-being, though the effect is not equally strong in all three receiving countries and differs by welfare domain (healthcare, childcare, unemployment benefits, social assistance, and state pensions). This is particularly true if migrants know their rights regarding healthcare. Policy advisors should therefore pay special attention to migrants’ access to information about social right policies in order to increase their well-being.